2019
DOI: 10.20471/acc.2019.58.02.12
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Foot Deformities in Young Schoolchildren in Slavonia

Abstract: SUMMARYThe aim of this study was to determine the occurrence of foot deformity in urban children, as well as possible generational and gender differences using graphic and angular methods. The sample of study subjects included 426 1st to 4th grade schoolchildren (7 to 10 years of age). Out of the total number of schoolchildren, 181 children (88 boys and 93 girls) were measured in 2005, and 244 children (122 boys and 123 girls) in 2011. The results indicated that the largest number of children had no noticeable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
3
2
1
1
Order By: Relevance
“…Similar to the results of other studies [14,16,17], we also detected a decreasing trend in the prevalence of childhood flat feet with increasing age. Between younger (11.3%) and older (8.2%) schoolchildren, were found statistically significant differences in the prevalence of flat foot (the greater number is present in earlier grades).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to the results of other studies [14,16,17], we also detected a decreasing trend in the prevalence of childhood flat feet with increasing age. Between younger (11.3%) and older (8.2%) schoolchildren, were found statistically significant differences in the prevalence of flat foot (the greater number is present in earlier grades).…”
Section: Discussionsupporting
confidence: 91%
“…Our study demonstrates that the prevalence of flat feet in schoolchildren is not influenced by gender, although the percentage distribution of flat feet was higher in (10.8%) than girls (8.7%). A few published studies also affirmed that the commonness of level flat feet in boys is marginally more than girls, yet without any significant statistical difference [16,17,18]. Opposite to our results, a study on 6.992 Poland children aged 8-12 years reported a significant positive correlation between gender and incidence of a flat foot, where flat feet were more in boys (6.2%) than girls (3.3%) [4].…”
Section: Discussioncontrasting
confidence: 55%
“…Discrepancies in the studies focused on assessing flatfootedness range from 4.7% to 75% [ 11 , 15 , 22 , 23 , 24 ]. Similar differences are notable with regard to assessing a hollow foot—ranging 9–66.55% [ 15 , 25 ]. The present study made use of four approaches in this assessment, with a view to establishing the overall reliability of the select indices under study.…”
Section: Discussionmentioning
confidence: 79%
“…One hour of effort also had a slight effect on the height of the arches of both feet. Bogut I. et al [ 30 ] conducted research on the occurrence of foot deformities in city children, as well as on possible generation and sex differences. The results of the research showed that the highest percentage of children did not have a noticeable foot deformity, so more than three-quarters of children in 2005 and 2011 had healthy feet.…”
Section: Discussionmentioning
confidence: 99%